Awareness, practices, attitudes, and barriers of telehealth in Saudi Arabia - Alharbi, Raed Abdullah (Journal of the Pakistan Medical Association, 2023)
Objective: To assess awareness level, practices, attitudes and barriers regarding telehealth among healthcare providers (HCPs) in Saudi Arabia. Method: This cross-sectional study was approved by institutional review board (IRB) at King Fahad Medical City, Riyadh, Saudi Arabia, from June 28 to September 18, 2022, and comprised HCPs at different hospitals across the country. Data was collected using an online questionnaire exploring the awareness level, practices, attitudes and barriers regarding telehealth. Data was analysed using Statistical Analysis System 9.4. Results: Of the 607 HCPs, 525(86.5%) were Saudi HCPs; 301(57.33%) males and 224(42.66%) females, with the largest age group being 31-40 years 218(41.52%). The remaining 82(13.5%) HCPs were non-Saudi HCPs; 43(52.43%) males and 39(47.56%) females, with the largest age group being 31-45 years 35(42.68%). Overall, there were 305(50.24%) health practitioners and most of the HCPs belonged to the Riyadh region 194(31.96%). (549)90.44% of HCPs were aware of telehealth, while (360)59.30% were actually practicing it. Also, (488)80.39% of HCPs believed that telehealth is a valid technology, while (443)72.98% believed telehealth is a reliable technology. Conclusion: Awareness regarding telehealth was high among HCPs meaning telehealth are progressively growing and spreading among HCPs and medical facilities in Saudi Arabia, who also found it valid and reliable. Key Words: Telehealth, Public health, Healthcare, Medical services, Health Informatics.